PENGARUH STIMULUS KUTANEUS TERHADAP PENURUNAN NYERI POST SECTIO CAESARIA DI RUANG MELATI LT 2 RSUD DR.SOEKARDJO KOTA TASIKMALAYA - Annisa Setywati; Neni Nuraeni; Rosy Rosnawanty (LPPM Universitas Muhammadiyah Tasikmalaya, 2018)
Post-operative of patients sectio caesaria will feel the pain. One of the non pharmacological therapies that can be used in cutaneous stimulus. Cutaneous stimulus is masage (sweep) back slowly. This aims to know the influence of cutaneous stimulus against the scale of pain the patient post operation sectio caesarea in Melati Room 2 Provincial Hospital dr. Soekardjo Tasikmalaya. Design research using One Group Pre-post test design, Experimental Design preresearch by sampling using the technique of accidental sampling with a total sample of 15 respondents. Pain was measured using the Numeric Pain Rating Scale (NPRS). The results of statistical tests by using the test for paired t test retrieved the value of ?-value 0.000. This means that there is influence the scale of pain before and after cutaneous stimulus. In therapy the non pharmacological techniques of cutaneous stimulus can be used to improve the quality of nursingcare in particular to lower pain scale in patients post operation sectio caesarea.